China sea pilot the north-western coast of Borneo, the Philippine Islands from Cape Buliluyan in Palawan to Cape Bojeador in Luzon, and the islands and dangers in the southern and eastern parts of the South China Sea (Admiralty charts and publications, admiralty sailing direction, NP31, 1998)
This Admiralty Sailing Directions covers the north western coast of Borneo, the Philippine Islands from Cape Buliluyan in Palawan to Cape Bojeador in Luzon, and the islands and dangers in the southern and eastern parts of the South China Sea.